Penerapan Pembelajaran Pendidikan Agama Islam Dalam Membentuk Karakter Pribadi yang Islami Di STAI Kuala Kapuas - Andri Suryani (AL-IBNOR, 2024)
This study discusses the strategy of Islamic religious education teachers in the teaching of Islamic Education as efforts to establish the Islamic personality ofthestudents in Stai kuala kapuas. This type of research is qualitative research. Interdisciplinary research approach used, among other things: management approach, pedagogical, sociological, and psychological. Sources of primary data from this study were teachers of Islamic education. Secondary data sources in this study a school profile data, theories on the concept of the learning strategies, Islamic religious of education theory, and the theory of the formation of Muslim personality. Data collection techniques using observation, interviews, and documentation. Data were analyzed using the stages of data reduction, data presentation, and conclusion. The research found that the learning strategies of Islamic education in shaping Muslim personality of students use two strategies of learning, ie learning direct and indirect learning.